Relationship between foliar trichomes of common bean genotypes, Phaseolus vulgaris L., and resistance to Diabrotica speciosa Germar, 1824(Coleoptera: Chrysomelidae) - Fachini de Oliveira Paron, Maria Jose [UNESP]; Lara, Fernando Mesquita [UNESP] (Univ Federal Lavras-ufla, 2005)
Considering that foliar pubescence may affect insect feeding preference on plant genotypes, the purpose of this study was to evaluate the influence of leaflet pubescence on resistance of common bean genotypes to D. speciosa. The experiments were conducted in a completely randomised design, with six treatments and eight replicates. The treatments were six common bean genotypes, Emgopa Ouro and IAPAR 57, from Mesoamerican domestication center (MA), Jalo Precoce, Goiano Precoce, PR 10595142 and PR 10595146 from Andean domestication center (AN). Each replicate consisted of one pot with 1.2 kg soil and a plant placed in a individual cage. The genotypes were submitted to feeding test 25 days after planting, when ten adults of D. speciosa, starved for 24 hours, were released for 72 hours in each cage. Damage was estimated by area of foliage consumed on each genotype. Trichomes on both the abaxial (AB) and adaxial (AD) leaf surfaces were counted using a stereomicroscope (40 X), on 1 cm(2) area, with the hooked and straight trichomes being counted on five leaflets/genotype. The MA genotype IAPAR 57 was the most preferred on feeding test, while the AN genotypes were less eaten by Dispeciosa. The genotypes showed variability aceading to density of trichomes on both surfaces. Andean genotypes showed no difference in unciform trichome densities on AD surface. The total number of straight and hooked trichomes on AB leaf surface suggests inverse relation between this characteristic and the area consumed by Diabrotica speciosa
Keywords: Pubescence; feeding preference; host plant resistance; common bean; Fabaceae